2017
DOI: 10.1097/tp.0000000000001840
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus Trough Concentration Variability and Disparities in African American Kidney Transplantation

Abstract: Background Low tacrolimus concentrations have been associated with higher risk of acute rejection, particularly within African-American (AA) kidney transplant recipients; little is known about intrapatient tacrolimus variabilities impact on racial disparities. Methods Ten year, single-center, longitudinal cohort study of kidney recipients. Intrapatient tacrolimus variability was assessed using the coefficient of variation (CV) measured between 1 month posttransplant and the clinical event, with a comparable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 53 publications
6
56
0
Order By: Relevance
“…In comparison, our study evaluated a larger cohort and focused on early TAC troughs and doses. A more recent study by Taber et al also included earlier intra‐patient TAC trough variability starting at one month prost‐transplant in a larger cohort and showed that trough variability was higher in AA (CV 39.9%) compared to non‐AA recipients (CV 34.8%), which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In comparison, our study evaluated a larger cohort and focused on early TAC troughs and doses. A more recent study by Taber et al also included earlier intra‐patient TAC trough variability starting at one month prost‐transplant in a larger cohort and showed that trough variability was higher in AA (CV 39.9%) compared to non‐AA recipients (CV 34.8%), which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Similar studies showed association between high intra‐patient TAC trough variability and acute rejection, decline in glomerular filtration rate, graft loss, or composites thereof . A study by Taber et al of TAC troughs beginning at 1 month post‐transplant showed that high trough variability was associated with a higher risk of acute rejection and graft loss. To our knowledge, no study has previously investigated the impact of intra‐patient variability in TAC dose on kidney transplant outcomes.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Both optimizing choice of calcineurin inhibitor and therapeutic serum drug level have been associated with decreasing rates of acute rejection . With respect to ancestry, race/ethnicity impacts CYP enzymatic expression, tacrolimus dose requirements, and rates of acute rejection that disproportionately affect African‐Americans . Rates of kidney allograft survival in African‐American recipients are lower than in their Caucasian counterparts by more than 5% at 5 years (OPTN data, 2008‐2015).…”
Section: Discussionmentioning
confidence: 99%
“…This difference in allele frequency results in a functional Cytochrome P450 3A5 isozyme (CYP3A5) enzyme in a majority of African Americans, while most Europeans do not have a functional enzyme. A recent study of tacrolimus dosing in 50 African Americans showed that the CYP3A5*1 allele is associated with normal function (also referred to as expressers), subtherapeutic concentrations, and higher dose requirements for tacrolimus compared with nonexpressers, i.e., patients with a CYP3A5*3/*3 diplotype …”
Section: Pharmacogenomics and Minority Populationsmentioning
confidence: 99%